2014
DOI: 10.1007/s10384-014-0363-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variable outcome of myopic choroidal neovascularization treated with ranibizumab

Abstract: Intravitreal ranibizumab resulted in long-term efficacy in the treatment of myopic CNV. However, some eyes may present a long-term relative decline in their initial visual gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
3
21
1
6
Order By: Relevance
“…Silva et al [15] reported a mean of 3.6 intravitreal ranibizumab injections at the 12-month follow-up. Similar data were found in the study by Cohen et al [25] with a mean intravitreal ranibizumab number of 3.5 (range 1–12) over a mean follow-up of 39.3 months. Pece et al [38] reported 2.3 intravitreal injections in the ranibizu­mab subgroup during 20-month follow-up; similarly, Iacono et al [16] reported a mean of 2.5 intravitreal rani­bizumab injections over 18 months.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Silva et al [15] reported a mean of 3.6 intravitreal ranibizumab injections at the 12-month follow-up. Similar data were found in the study by Cohen et al [25] with a mean intravitreal ranibizumab number of 3.5 (range 1–12) over a mean follow-up of 39.3 months. Pece et al [38] reported 2.3 intravitreal injections in the ranibizu­mab subgroup during 20-month follow-up; similarly, Iacono et al [16] reported a mean of 2.5 intravitreal rani­bizumab injections over 18 months.…”
Section: Discussionsupporting
confidence: 79%
“…However, the present report revealed that visual acuity gain (13.7 ETDRS letters) at the 2-year follow-up was better than that in the series by Ruiz-Moreno et al [22]. These data are probably due to higher baseline visual acuity in that study (60.5 letters) compared to our series (56.2 letters), a lower baseline BCVA being more likely to show a higher improvement [25]. …”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Verschiedene Langzeit-Nachbeobachtungsstudien konnten zeigen, dass die zunehmende Verschlechterung der bestkorrigierten Sehschärfe (BCVA, best corrected visual acuity) in myopen Augen durch eine Makulaatrophie bedingt ist [22,23,24,25,26]. In ihren Untersuchungen zur Beurteilung der Langzeitwirksamkeit von intravitreal verabreichten Anti-VEGF-Wirkstoffen als Primärtherapie bei mCNV zeigten Lai et al [27] sowie Franqueira et al [28], dass Ranibizumab eine erfolgreiche therapeutische Option darstellt und mit einer bis zu 2 bzw.…”
Section: Introductionunclassified